Assessment of magnitude of physical activity among rural high school children of Nelamangala taluk, Bengaluru: a cross sectional study - Kumar S., Nandish; Jadhav, Jyothi; T. S., Ranganath; ., Vishwanatha (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, more than two thirds of adolescents aged 11-17 years have insufficient physical activity. Though data on prevalence of physical activity among adolescents with reference to WHO criteria are available, very few studies have assessed the magnitude of physical activity. Hence, the study was conducted to assess the magnitude of physical activity among rural high school children of Nelamangala Taluk, Bengaluru. Methods: A cross sectional study was conducted among 200 high school students from 6 co-education schools. Magnitude of physical activity was assessed using physical activity questionnaire for adolescents (PAQ-A), a self-reported, validated questionnaire. Results: Mean age of the study participants was 14.35 years. 112 (56%) of them were female and 123 (61.5%) of them were studying in 10th standard. 100 (50%) of them were from government or aided school. Final Physical activity score of study participants was 2.39±0.64. There was a statistically significant difference (p<0.05) in the final physical activity score between males and females. Government or aided school participants had a better final score than those of private school and the difference was statistically significant. Final physical activity score decreased with their promotion to higher class. There was no significant difference between activity levels during physical education class across variables like sex, class studying and type of school. Conclusions: Physical activity was better among males, government school participants and those studying in lower class in comparison to their counterparts. Majority of this difference can be attributed to activities happening beyond the school hours.